Transforming IQ into "orthopédie mentale" : an introduction to A. Binet and V. Vaney on mental orthopedics /: an introduction to A. Binet and V. Vaney on mental orthopedics. ([2017]) - Siemsen, Hayo; Testelin, John; Martin-Hansen, Lisa M; Siemsen, Karl Hayo; Andrieu, Bernard, 1959-; Fèvre, Jean-Marie
No abstract available